2022
DOI: 10.1039/d2an00283c
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic flow cytometry for blood-based biomarker analysis

Abstract: Flow cytometry has proven its capability for rapid and quantitative analysis of individual cells and the separation of targeted biological samples from others. The emerging microfluidics technology makes it possible...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 218 publications
0
14
0
Order By: Relevance
“…151,152 MFCMs still require dilution and/or a sample preparation process for the analysis of whole blood; hence, a more detailed discussion of these has not been included in this review. 150,153,154 Perhaps the sample preparation technologies discussed here could be integrated to further develop MFCMs to separate blood cells from plasma/serum and potentially analyze both components simultaneously.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…151,152 MFCMs still require dilution and/or a sample preparation process for the analysis of whole blood; hence, a more detailed discussion of these has not been included in this review. 150,153,154 Perhaps the sample preparation technologies discussed here could be integrated to further develop MFCMs to separate blood cells from plasma/serum and potentially analyze both components simultaneously.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Some developments in microfluidic devices involve the isolation and analysis of blood cells and/or extracellular vesicles, which can aid in applications for liquid biopsies and cytopathology. Flow cytometry capabilities, such as single-cell characterization and sorting, have been implemented into microfluidic devices to make portable instruments targeted at POC applications. Recent advancements toward developing microfluidic flow cytometers (MFCMs) were summarized by Zhang et al and concluded that MFCMs do not offer a significant advantage over traditional flow cytometry, since the current detection and sorting subsystems need to be further developed to meet the cost, portability, and performance required for use in POC settings . The fabrication processes for MFCMs have been discussed in other reviews, with the general outcomes being that they are too complex and expensive for large-scale manufacturing.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, conventional flow cytometry is bulky, complex, and requires highly skilled personnel. With the development of microfluidic technology, microfluidic flow cytometry (MFCM) has been combined with flow cytometry to achieve powerful single cell focusing, detection, and sorting, which has been proven in various biological applications [ 3 ], including single-cell RT-PCR [ 4 ], stem cell screening [ 5 ], protein analysis [ 6 ], etc. While MFCM has proven to be a powerful tool for single-cell manipulation and analysis in medical diagnostics and animal cell studies, similar work on plant-cell properties is still far behind.…”
Section: Introductionmentioning
confidence: 99%